Assessment of Mg(OH)2/TiO2 coating in the Mg‐Ca‐Zn alloy for improved corrosion resistance and antibacterial performance - Leonardo Hernández; Jesús Ramón-Sierra; Montserrat Soria-Castro; Ángel Bacelis; Geonel Rodríguez-Gattorno; Elizabeth Ortiz-Vázquez; Gloria Acosta (Journal of Magnesium and Alloys, 2023)
The high activity of metallic magnesium and alloys limits its potential in biomedical applications; in recent years, extensive efforts have been devoted to modulating this reactivity. In this work, we present Mg(OH)2 and TiO2 barrier coatings to reduce the degradation of magnesium alloy (Mg-Ca-Zn) surfaces. These coatings were deposited by the anodization method and the spin-coating technique, respectively. The anodized layer was coated with TiO2 generated from the hydrolysis of 3% weight of TTIP (Ti[OCH(CH3)2]4, Titanium(IV) isopropoxide) in 2-Propanol deposited by the spin-coating method. Studying the degradation in Ringer's solution by electrochemical impedance spectroscopy and OCP revealed a 98% reduction in pittings in uncoated samples after 14 days of immersion. The pH measurements revealed that the TiO2 coating reduced the alkalization of the physiological environment, keeping the pH at 6.0 values. In vitro studies of two types of bacteria (E. coli and S. aureus) exhibited zones of inhibition in the agar and activity bactericidal (kill time test). The mechanisms behind the improved degradation resistance and enhanced antibacterial activity are presented and discussed here. Surface modification with Mg(OH)2/TiO2 coatings is a promising strategy to control the biodegradation of magnesium implants for bone regeneration.